Psychological Impact of the COVID-19 Pandemic on Pregnant Women - Buonsenso, Danilo; Malorni, Walter; Turriziani Colonna, Arianna; Morini, Sofia; Sbarbati, Martina; Solipaca, Alessandro; Di Mauro, Antonio; Carducci, Brigida; Lanzone, Antonio; Moscato, Umberto; Costa, Simonetta; Vento, Giovanni; et al. (Frontiers in Pediatrics, 2022)
Abstract Objective. To assess the impact of the COVID-19 pandemic on mental health, type of delivery and neonatal feeding of pregnant women with or without SARS-CoV-2 infection during gestation. Study Design. An online, anonymous survey was distributed to mothers that delivered during the COVID-19 pandemic. Results. The survey was completed by 286 women, 64 women (22.4%) had COVID-19 during pregnancy. Women that had SARS-CoV-2 infection during pregnancy or at time of delivery had a significantly higher probability of being separated from the newborn (p< 0.0001) and a significantly lower probability of breastfeeding (p< 0.0001). The Edinburg Postnatal Depression Scale, to assess if mothers had symptoms of postnatal depression, showed that items suggestive of postnatal depression were relatively frequent in the whole cohort. However, women with SARS-CoV-2 infection during pregnancy reported higher probability of responses suggestive of postnatal depression in 8 out of 10 items, with statistically significant differences in three items. Conclusion. The COVID-19 pandemic affected type of delivery and breastfeeding of pregnant women, particularly when they had SARS-CoV-2 infection. This, in turn, had an impact on psychological status of the interviewed mothers, aspects that could benefit of special support.